STRATEGI GOAL SETTING UNTUK MENINGKATKAN MOTIVASI BELAJAR MAHASISWA PTM UNNES MATA KULIAH KINEMATIKA DAN DINAMIKA - A, Dony Hidayat; W, Rahmat Doni (Universitas Negeri Semarang, 2013)
The purpose of this study was to determine the effect of goal setting methods on learning outcomes of students of PTM in a kinematics and dynamics course. The subjects were PTM students even semester of 2011/2012, Engineering Faculty UNNES. This research is motivated by the lack of student learning outcomes in the earlier half of the semester-indicated because of lack of motivation in learning. This study used an experimental method. The population was 45 students in one class, divided into 2 groups, control class and experiment. Each subject in the study period of 7 lessons given the task to make a goal at the end of the course as well as a weekly goal. Series of goals made by the subject is placed on the the wall to give positive affirmations. At presence measurement, goal setting gives a significant number to the difference in the number of student attendance. Data for quiz grades showed that the effect of this method was not significant. This study shows that the goal setting can be applied to increase student motivation. It would be better if supported by increasing self-awareness through the control of behavior.